The Marionette of Heinrich von Kleist: A Dancing Model. Issue 2 (4th May 2019) - Vittori, Giulia
Abstract: Heinrich von Kleist's conception of the marionette, as articulated in his renowned essay "The Puppet Theatre, " remains provocative today. With the marionette, I argue, Kleist drafts for the actor a theoretical model informed by grace. In Kleist's reconsideration of the process of performing, dance plays a significant part. Dance also leaves significant traces in Kleist's plays, particularly Penthesilea and Katie of Heilbronn, two complementary examples, I posit, in which performatic dramaturgy "choreographs" the marionette's behavior. Working across theater and dance, and mingling theory and practice, Kleist anticipates a contemporary vision of intermedial creation.